2014
DOI: 10.2320/matertrans.m2013274
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Microstructure on Mg Scroll Forging under Warm Forming Condition

Abstract: Magnesium (Mg) alloys have attracted considerable interest for various applications, including those in the automotive and electronics industries, because of their high specific strength, excellent thermal conductivity, and recycling capability in comparison with commonly used aluminum alloys and steels for structural materials. One of the core parts in the compressor unit of an automobile is the scroll rotor, which is assembled with two scrolls, a rotating orbit scroll on the fixed scroll, to compress the ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…That is why much higher mechanical properties including the YS and the UTS are shown for the specimens forged at 523 K than for those forged at 623 K since the fraction of recrystallized grains at 523 K is larger than that at 623 K. Therefore, it can be concluded that the warm-forging temperature should be reduced to as low as possible to obtain the mechanical properties of the as-forged product comparable with those of magnesium alloys. Since there has been extensive research progress on the improvement in the formability and the strength of magnesium alloys by controlling the initial texture and by adopting a twin-induced microstructure in the starting billet, 1618 lightweight design of the control arm using magnesium alloys is worthy of note for the future.…”
Section: Resultsmentioning
confidence: 99%
“…That is why much higher mechanical properties including the YS and the UTS are shown for the specimens forged at 523 K than for those forged at 623 K since the fraction of recrystallized grains at 523 K is larger than that at 623 K. Therefore, it can be concluded that the warm-forging temperature should be reduced to as low as possible to obtain the mechanical properties of the as-forged product comparable with those of magnesium alloys. Since there has been extensive research progress on the improvement in the formability and the strength of magnesium alloys by controlling the initial texture and by adopting a twin-induced microstructure in the starting billet, 1618 lightweight design of the control arm using magnesium alloys is worthy of note for the future.…”
Section: Resultsmentioning
confidence: 99%
“…Skubisz et al [41] analyzed the forming behavior of wrought AZ61 (hot deformed to 0. Yoon et al [70] investigated the forming behavior and process parameters of extruded AZ61 forging stock with compression testing and simulation. Forging trials were done at 350 • C with a speed of 32 mm s −1 .…”
Section: Az61mentioning
confidence: 99%
“…For magnesium alloys, Zheng [12] and Zhang [13] investigated the fatigue crack growth and failure behavior of AZ31B sheets. Tari [14] and Yooh [15] demonstrated that the fracture mechanism of AZ31B sheets varied with the temperature. Transformation-induced plasticity (TRIP) steels and dual-phase (DP) steels are two valuable high strength steels that can be stamped at room temperature.…”
Section: Introductionmentioning
confidence: 99%